Implementation of The Concept of Restorative Justice in Overcoming Over Capacity in Correctional Institutions - Prio Budi Tri Utomo; Yusuf Saefudin (UM Purwokerto Press, 2023)
The concept of restorative justice as a form of out-of-court settlement is needed to overcome various problems beyond the capacity of prisoners in prisons. Because the overcapacity of prisoners can cause many kinds of problems that exist in correctional institutions. Overcapacity in correctional institutions is influenced by several factors, one of which is the high rate of imprisonment used in existing regulations. The application of the concept of restorative justice can reduce the use of imprisonment to overcome overcapacity in correctional institutions. The research method of legal writing is normative legal research. Restorative justice policies are regulated by international legal instruments and national laws. The results of the study show that the policy of building restorative justice in combating prisoner overcrowding has been contained in the 2000 Vienna Declaration, the Minimum Standard Rules for the Treatment of Prisoners, Law No. December 1995 on Corrections, Perkapolri No. 6 of 2019, Perjak No. 15 of 2020, MARI Badilum Decree No. 1691/DJU/SK/PS.00/12/2020). The implementation of the concept of restorative justice aims to overcome overcapacity in correctional institutions.